Use of advantages of pulling method for erection of large-span coatings - IGNATENKO, Oleksandr (Ways to Improve Construction Efficiency, 2024)
Based on analysis of the features of the known variant of lifting of large-span coatings through the pulling method, a new technological solution for erecting coatings using lifting modules was developed. According to the developed solution, first, by methods of free lifting using self-propelled boom cranes, paired columns of the frame, inter-column beams and bundles are mounted. Guide profiles are fixed on inner surfaces of paired columns. Lifting modules are mounted between paired columns on foundations. Support frames are fixed on upper platforms of lifting modules. The large-span block of coatings is enlarged on mounting stands provided that bearing crossbars of covering rest on support frames. The moving of coating girders to design height is performed by pushing method. In the process of vertical movement of the load from the crossbars of the coating, the lower and upper platforms of the lifting module are alternately perceived, which interact with the guide profiles. After moving the roof girders to the design mark, support frames are fixed between the heads of paired columns. Unloaded lifting modules are moved to foundations using guide profiles and dismantled. The use of the developed structural and technological solution allows to reduce the volume of top-climbing labor-intensive dangerous installation work before the operations for the final fastening of the crossbars of the supporting frames of the coating between the heads of the paired columns of the frame. All components of the process of moving the coating from the foundation level to the design height using a lifting module are automated. Also, the developed solution can significantly reduce the overall time for the construction of coatings. All installation work on the enlargement of coatings on stands using self-propelled boom cranes and a set of works on the vertical movement of coatings using lifting modules are carried out on the sites, dimensions of which do not exceed overall dimensions of large-span erected coatings.